Characterizing SSTR2 expression and modulation for targeted imaging and therapy in preclinical models of triple-negative breast cancer - Shannon E. Lynch; Corinne I. Crawford; Hailey A. Houson; James M. Omweri; Piyasuda Pukkanasut; Carlos A. Gallegos; Jason D. Whitt; Renata Jaskula-Sztul; Suzanne E. Lapi; Anna G. Sorace (Scientific Reports)
Abstract Patients with breast cancer which lack molecular targets, such as human epidermal growth factor receptor 2 (HER2) or hormone receptors, have limited access to targeted therapies. Somatostatin receptor 2 (SSTR2) is overexpressed in some cancers, and SSTR2-targeted radiopharmaceuticals are FDA-approved for theranostic targeted imaging and therapy in neuroendocrine tumors (NETs). Importantly, histone deacetylase (HDAC) inhibitors can epigenetically modulate SSTR2 expression in NETs with low or variable basal expression. The goal of this study is to characterize SSTR2 basal expression and induction via HDAC inhibition as a potential target for imaging and therapy in preclinical models of triple-negative breast cancer (TNBC). SSTR2 expression in mouse samples was assessed via Western blot and immunohistochemistry. Real-time quantitative PCR (qRT-PCR), flow cytometry, and cell binding assays were utilized to determine if HDAC inhibition can upregulate SSTR2 expression. [68Ga]Ga-DOTATATE positron emission tomography (PET) imaging, which targets SSTR2, was used to non-invasively characterize SSTR2 expression and variability in the EO771 and 4T1 TNBC models before and after HDAC inhibition. These studies demonstrate that HDAC inhibition can upregulate SSTR2 at the transcriptional, translational, and functional levels in breast cancer. Importantly, SSTR2 expression can be characterized non-invasively via PET imaging and modulation with HDAC inhibitors can be monitored longitudinally. Our findings highlight SSTR2 as a promising therapeutic molecular target in TNBC.